The criteria describing the need for highway reconstruction based on the theory of traffic flows and repay time - Beljatynskij, Andrey; Kuzhel, Nina; Prentkovskis, Olegas; Bakulich, Olena; Klimenko, Irina (Transport, 2009)
General data on the network of Ukrainian highways are presented. The analysis of design methods of highway reconstruction based on the theory of traffic flows and economic calculations of its repay time is made. The relationship between traffic intensity and speed is shown by considering the theory of traffic flows. The methods, taking into account the principle of effectiveness of highway reconstruction based on its repay time, are discussed.First published online: 27 Oct 2010